Contaminants and Where to Find Them: Microbiological Quality Control in Axenic Animal Facilities - Lebeuf, Maria; Turgeon, Nathalie; Faubert, Cynthia; Pleau, Alexandre; Robillard, Justin; Paradis, Éric; Marette, André; Duchaine, Caroline (Frontiers in Microbiology, 2021)
The use of axenic animal models in experimental research has exponentially grown in the past few years and the most reliable way for confirming their axenic status remains unclear. It is especially the case when using individual ventilated positive-pressure cages such as the Isocage. This type of cage are at a greater risk of contamination and expose animals to a longer handling process leading to more potential stress when opened compared to isolators. The aim of this study was to propose simple ways to detect microbial contaminants with Isocages type isolator resulting by developing, validating and optimizing three different methods (culture, microscopy, molecular). These three approaches were also tested in situ by spiking 21 axenic mice with different microorganisms. Our results suggest that the culture method can be used for faeces and surface station (IBS) swabs exclusively (in Brain Heart Infusion for 7 days at 25°C and 37°C in aerobic conditions, and at 30°C in anaerobic conditions), while microscopy (wet mounts) and molecular method (quantitative PCR) were only suitable for faecal matter analyses. In situ results suggests that the culture and molecular methods can detect up to 100% of bacterial contamination events while the microscopy approach generates many erroneous results when not performed by a skilled microscopist. In situ results also suggest that when an axenic mouse is contaminated by a microbial agent, the microorganism will colonize the mouse to such an extent that detection is obvious in four days, in average. This report validates simple but complimentary tests that can be used for optimal detection of contaminants in axenic animal facilities using Isocage type isolators.